The analysis of primary circulation flow patterns and environmental parameter characteristics of short-duration heavy precipitation during the warm seasons in the Western Tianshan Mountains, Xinjiang - Li, Jiangang; Zhu, Xiaomei; Jiang, Cailian; Tong, Zepeng; Bai, Ting; Li, Yang (Frontiers in Earth Science, 2026)
Based on a decade of observational and reanalysis data, this study systematically analyzes the main atmospheric circulation patterns and environmental conditions linked to warm-season short-duration heavy precipitation in the Western Tianshan Mountains, Xinjiang. Three dominant circulation patterns are identified: the Low-Trough pattern, the Low-Vortex pattern, and the Eastward-moving Waves pattern. The Low-Trough and Low-Vortex patterns are further divided into subtypes based on the location of the trough or vortex, while the Eastward-moving Waves pattern is characterized by a zonal flow with eastward-moving short-wave disturbances. Short-duration heavy precipitation shows a clear daily cycle across all patterns, with the highest frequency occurring from afternoon to early evening. Rainfall tends to concentrate on windward slopes and in valleys. The exact location of precipitation is influenced by the pressure gradient and wind direction—shifting northward under stronger westerly winds and southward under weaker southwesterly flows. The Low-Vortex pattern exhibits the strongest coupling between upper- and low-level jets and the most extensive jet coverage, providing optimal lifting conditions for intense and widespread rainfall. The Low-Trough pattern shows moderate jet coupling, while the Eastward-moving Waves pattern relies on weak upper-level forcing, resulting in more limited precipitation. Moderate vertical wind shear is common during these events. All patterns display a consistent vertical structure of pseudo-equivalent potential temperature, characterized by a “high–low–high” pattern. The Low-Vortex pattern features a prominent upper-level high-value layer and a shallow mid-level cool layer, favoring intense convection. The Low-Trough pattern shows strong heating in both the upper and lower levels but a more distinct mid-level cool zone, enhancing atmospheric instability. In contrast, the Eastward-moving Waves pattern has a thick mid-level cool layer and weak low-level heating, leading to the weakest convective potential. The Low-Vortex and Low-Trough patterns are associated with higher low-level moisture, while the drier Eastward-moving Waves pattern requires greater convective available potential energy and lower convective inhibition to initiate convection.